Structural elucidation of the cis-prenyltransferase NgBR/DHDDS complex reveals insights in regulation of protein glycosylation - Edani, Ban H. (Proc Natl Acad Sci U S A, 2020)
Cis-prenyltransferase (cis-PTase) catalyzes the rate-limiting step in the synthesis of glycosyl carrier lipids required for protein glycosylation in the lumen of endoplasmic reticulum. Here, we report the crystal structure of the human NgBR/DHDDS complex, which represents an atomic resolution structure for any heterodimeric cis-PTase. The crystal structure sheds light on how NgBR stabilizes DHDDS through dimerization, participates in the enzyme’s active site through its C-terminal -RXG- motif, and how phospholipids markedly stimulate cis-PTase activity. Comparison of NgBR/DHDDS with homodimeric cis-PTase structures leads to a model where the elongating isoprene chain extends beyond the enzyme’s active site tunnel, and an insert within the α3 helix helps to stabilize this energetically unfavorable state to enable long-chain synthesis to occur. These data provide unique insights into how heterodimeric cis-PTases have evolved from their ancestral, homodimeric forms to fulfill their function in long-chain polyprenol synthesis.